The efficacy and safety of tislelizumab combined with weekly nab-paclitaxel, carboplatin, and cetuximab as first-line treatment for recurrent or metastatic head and neck squamous cell carcinoma: a real-world study - Ouyang, Zhanyong; Zhang, Linting; Wang, Feng; Chen, Meijing; Cheng, Boran; Yang, Fang; Lai, Wenjuan; Gao, Jing; Wang, Shubin; Tong, Gangling (Frontiers in Immunology, 2026)
BackgroundPatients with recurrent or metastatic head and neck squamous cell carcinoma (R/M-HNSCC) face poor prognosis. This study evaluated the efficacy and safety of a novel first-line regimen combining tislelizumab, nab-paclitaxel, carboplatin, and cetuximab (TPCE) in R/M-HNSCC.MethodsIn this retrospective study, 39 patients with R/M-HNSCC received tislelizumab (200 mg, day 1), nab-paclitaxel (125 mg/m2, days 1, 8), carboplatin (AUC = 2, days 1, 8), and cetuximab (400 mg/m2 loading dose, then 250 mg/m2 weekly, day 1) every 21 days for up to six cycles. Patients achieving stable disease or better continued maintenance therapy with cetuximab and tislelizumab until disease progression or unacceptable toxicity. The primary endpoint was objective response rate (ORR); secondary endpoints included disease control rate (DCR), duration of response (DOR), progression-free survival (PFS), overall survival (OS), and safety.ResultsThe TPCE regimen demonstrated significant antitumor activity, with an ORR of 82.1% and a DCR of 97.4%. With a median follow-up of 27.0 months (95% confidence interval [CI]: 23.6-30.4 months), the median DOR was 12.5 months (95% CI: 9.5-15.5 months), the median PFS was 14.0 months (95% CI: 11.0-17.1 months), and the median OS was 27.0 months (95% CI: 20.7-33.3 months). The 2-year PFS rate was 31.3 ± 7.8%, and the 2-year OS rate was 58.4 ± 8.4%. Subgroup analysis revealed a significantly higher ORR in patients with tongue carcinoma (P = 0.023). Lower baseline neutrophil-to-lymphocyte ratio (NLR, P = 0.044), systemic immune-inflammation index (SII, P = 0.044), and albumin level (P = 0.044) were correlated with improved ORR. A reduction in NLR after two treatment cycles was also associated with higher ORR (P = 0.037). Multivariate analysis identified baseline hemoglobin-albumin-lymphocyte-platelet (HALP) score as an independent prognostic factor for PFS (HR: 2.919; 95% CI: 1.153-7.391; P = 0.024), while primary tumor location (HR: 3.160; 95% CI: 1.205-8.282; P = 0.019), HALP score (HR: 3.541; 95% CI: 1.287-9.744; P = 0.014), and post-treatment SII changes (HR: 0.370; 95% CI: 0.151-0.906; P = 0.030) were independent predictors for OS. Grade 3–4 treatment-emergent adverse events were primarily hematologic, with granulocytopenia (38.5%) being the most common. Most immune-related adverse events were grade 1-2, with hypothyroidism (33.3%) occurring most frequently.ConclusionThe TPCE regimen demonstrated robust antitumor efficacy and a manageable safety profile as a first-line treatment for R/M-HNSCC. Baseline and dynamic inflammatory-nutritional markers may serve as predictive and prognostic indicators, supporting clinical decision-making for this patient population. Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR2500108877.